Ear and temporal bone pathology: is anything new?. Issue 5 (May 2021) - Sandison, Ann; Kennedy, Robert
Abstract: The ear and temporal bone are a challenging areas for the diagnostic pathologist. The anatomy is complex and lesions may be small and relatively inaccessible. Many tumours occurring at this site are rarely encountered. Biopsy tissue samples may be crushed, small and often associated with bone, which complicates processing. Correlation with imaging is essential and interpretation often requires specialist expertise. In this article selected lesions are discussed in order to illustrate diagnostic difficulty the surgical pathologist encounters with small biopsies and on approaching the cut up of complex resection specimens from this site. The aim is to raise awareness of the recently introduced ICCR minimum data set for the reporting of tumours from ear and temporal bone and to alert readers to the discovery of new entities in middle ear investigated by novel molecular diagnostic techniques.